Faktor-faktor yang memengaruhi agresivitas pajak pada industri manufaktur tahun 2017-2021 - Gulam, Rizal; Pangestuti, Dinik Fitri Rahajeng (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to determine the influence of gender of directors, independent commissioners, audit committee, profitability and leverage on tax aggressiveness. This study is quantitative research using multiple linear regression techniques using a purposive sampling method based on predetermined criteria. The object of this research is manufacturing companies in the consumer goods industrial sector 2017-2021. This research uses panel data with a total of 170 observations from a sample of 34 companies. The results of the study show that women are more careful in making decisions but the results obtained are that gender cannot affect tax aggressiveness. Independent commissioners, in law are organs that must exist, but cannot influence tax aggressiveness because companies only want to comply with regulations. Leverage cannot reduce tax aggressiveness because high leverage will create high risks. But the audit committee and profitability can reduce the aggressiveness of the company because the audit committee can assist the commissioner in supervising, and profitability can reflect the company's financial well-being. Audit committee and profitability have a positive effect on tax aggressiveness. Gender of directors, independent commissioners and leverage have no effect on tax aggressiveness.